Archaeological Excavations of Antelope Creek Ruins and Alibates Ruins, Panhandle Aspect, 1938-1941 - Baker, Ele M.; Baker, Jewel A.; Panhandle Archeological Society (Panhandle Archeological Society, 2000)
Final Report Archeological Survey West Texas State Archeological Project 9249 and State Application 30976 by Ele M. Baker and Jewel A. Baker, 1938-1941. Overview of unique ruins of the panhandle, Alibates ruins, Antelope Creek ruins, and the Canadian River Valley.